Effect of ratio Pluronic P123 and gelatin on titania as a catalyst in methylene blue degradation - Ulfa, Maria; Pangestuti, Indriyani (Communications in Science and Technology, 2025)
This study explores the influence of the gelatin-to-Pluronic P123 molar ratio on the synthesis, structural properties, and photocatalytic performance of titania for methylene blue degradation. Gelatin, employed as a biotemplate alongside Pluronic P123, effectively modulates the physicochemical characteristics of titania. As the gelatin content increases, significant changes are observed in oxygen incorporation, pore morphology, and crystallinity. Energy-dispersive X-ray spectroscopy (EDX) reveals a progressive increase in surface oxygen content from 10% (T-Gl) to 29% (T-Gh), indicating strong interactions between gelatin’s NH? groups and titanium species. FTIR analysis confirms enhanced Ti–O–Ti bonding, with peak transmittance intensities reaching 79.857% in T-Gh. Nitrogen adsorption-desorption measurements verify mesoporosity across all samples, with pore diameters ranging from 12.4 nm to 14.8 nm and surface areas from 27.69 to 31.67 m²/g. Crystallite sizes, determined by XRD, range between 4.27 nm and 8.56 nm, while the crystallinity varies from 45.81% to 54.55%. Despite having a lower surface area, T-Gm exhibits excellent photocatalytic efficiency (90.23%) due to favorable pore and crystallite characteristics. T-Gh demonstrates the highest performance (92.90%), attributed to its oxygen-rich surface, moderate crystallinity, and balanced mesoporous framework that enhances charge separation and dye adsorption. These findings underscore the critical role of gelatin-to-P123 ratio control in tailoring structural and surface functionalities of titania, thereby offering a sustainable strategy for designing efficient photocatalysts for environmental remediation. The developed biotemplated synthesis approach not only enhances photocatalytic performance but also promotes the use of eco-friendly and cost-effective materials, making it highly beneficial for scalable applications in wastewater treatment.